2020
DOI: 10.3390/ijms21020569
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1, A Double-Edged Sword in Cancer

Abstract: Claudins, a group of membrane proteins involved in the formation of tight junctions, are mainly found in endothelial or epithelial cells. These proteins have attracted much attention in recent years and have been implicated and studied in a multitude of diseases. Claudins not only regulate paracellular transepithelial/transendothelial transport but are also critical for cell growth and differentiation. Not only tissue-specific but the differential expression in malignant tumors is also the focus of claudin-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 161 publications
(221 reference statements)
1
75
0
Order By: Relevance
“…CLDN1 is necessary to regulate physiological barrier function in various tissues, but its pathophysiological role in cancer is controversial [ 23 ]. CLDN1 up-regulates invasive activity in the colorectal cancer cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLDN1 is necessary to regulate physiological barrier function in various tissues, but its pathophysiological role in cancer is controversial [ 23 ]. CLDN1 up-regulates invasive activity in the colorectal cancer cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, claudins are emerging targets for therapeutic approaches and the elucidation of cancer malignancy, as they have been shown to be causally linked to mesenchymal transition [ 45 ]. Especially, on the example of claudin-1, it becomes clear that it can be involved in different ways in cancer development and that the generation of therapeutics relies on further investigations that explore the involvement of the respective claudins in the different types of cancer [ 46 ].…”
Section: Tj Proteins and Cancermentioning
confidence: 99%
“…CLDNs frequently show aberrant expression and/or subcellular localization in a wide variety of cancers, resulting in either promotion or repression of tumor progression [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], hypothetically due to dysregulated CLDN signaling. We previously reported that high CLDN6 expression in endometrial cancer is an independent prognostic factor that is significantly associated with several clinicopathological variables [ 23 ].…”
Section: Introductionmentioning
confidence: 99%